New taxonomic and nomenclatural data on Sarcophaga (Heteronychia) (Diptera: Sarcophagidae), with description of six new species - Whitmore, Daniel (Zootaxa, 2011)
This paper presents new data on Sarcophaga (Heteronychia). Six species are described as new: Sarcophaga (Heterony- chia) anatolica sp. nov. from Asiatic Turkey, S. (H.) lejlekensis sp. nov. from Kyrgyzstan, S. (H.) mediterranea sp. nov. from mainland Italy, Sicily and Croatia, S. (H.) rosellensis sp. nov. from central Italy, S. (H.) tetrix sp. nov. from Sicily, and S. (H.) tunisiae sp. nov. from Tunisia. Two new replacement names are proposed: Sarcophaga (Heteronychia) hellenica, nom. nov. for S. (H.) vervesi (Povolný, 1996) (junior secondary homonym of Kozlovea vervesi Nandi, 1993), and S. (H.) tangerensis, nom. nov. for S. (H.) amica (Peris et al., 1998) (junior secondary homonym of Phallosphaera amica Ma, 1964). Sarcophaga (Heteronychia) belanovskyi (Verves, 1973), S. (H.) helenae (Trofimov, 1948) and S. (H.) nanula (Povolný, 1999) are resurrected as valid, and the last (originally proposed as a subspecies) is given species rank. Sarcophaga amita Rondani, 1860 and S. bezziana Böttcher, 1913 are transferred from subgenus Discachaeta Enderlein to subgenus Heteronychia Brauer & Bergenstamm, subg. comb. nov. Thirty-nine new synonymies are established: Shoachaeta Lehrer, 1997 with Heteronychia Brauer & Bergenstamm, 1889, syn. nov.; Ashlaiana Lehrer, 1998 with Heteronychia Brauer & Bergenstamm, 1889, syn. nov.; Heteronychia iubita Lehrer, 1999 with Sarcophaga (Heteronychia) ancilla Rondani, 1865, syn. nov.; Spatulapica lucentina Lehrer & Martínez-Sanchez, 2001 with S. (H.) ancilla Rondani, 1865, syn. nov.; Heteronychia (Heteronychia) povolnyi Mihályi, 1975 with S. (H.) belanovskyi (Verves, 1973), syn. nov.; Sarcophaga benaci var. tenuiforceps Böttcher, 1913 with S. (H.) benaci Böttcher, 1913, syn. nov.; Heteronychia (Heteronychia) vachai Povolný, 1987 with S. (H.) benaci Böttcher, 1913, syn. nov.; Shoachaeta cornogranda Lehrer, 2009 with S. (H.) bezziana Böttcher, 1913, syn. nov.; Pierretia (Pandelleola) taurica Rohdendorf, 1937 with S. (H.) boettcheri Villeneuve, 1912, syn. nov.; Heteronychia (Pandelleola) gaspari Lehrer, 1977 with S. (H.) boettcheri Villeneuve, 1912, syn. nov.; Heteronychia bodediana Lehrer, 1998 with S. (H.) boettcheri Villeneuve, 1912, syn. nov.; Ashlaiana shakrana Lehrer, 1998 with S. (H.) boettcheri Villeneuve, 1912, syn. nov.; Pandelleola caraormana Lehrer, 2008 with S. (H.) boettcheri Villeneuve, 1912, syn. nov.; Heteronychia (Heteronychia) morenita Peris, González-Mora & Mingo, 1998 with S. (H.) chiquita (Peris, González-Mora & Mingo, 1998), syn. nov.; Heteronychia cullottorum Povolný, 2005 with S. (H.) consanguinea Rondani, 1860, syn. nov.; Heteronychia (Eupierretia) spatulifera Chen & Lu, 1981 with S. (H.) curvifemoralis (Li, 1980), syn. nov.; Heteronychia (Spatulapica) kovalae Verves, 1979 with S. (H.) depressifrons Zetterstedt, 1845, syn. nov.; Heteronychia dimioniphalla Lehrer, 1996 with S. (H.) dissimilis Meigen, 1826, syn. nov.; Heteronychia (Eupierretia) macedonica Povolný, 1996 with S. (H.) enderleini Jacentkovský, 1937, syn. nov.; Devriesia weberi Lehrer, 1995 with S. (H.) ferox Villeneuve, 1908, syn. nov.; Heteronychia (As- celoctis) perplexa Peris, González-Mora & Mingo, 1996 with S. (H.) ferox Villeneuve, 1908, syn. nov.; Pandelleola resnikae Lehrer, 1996 with S. (H.) filia Rondani, 1860, syn. nov.; Heteronychia fugitiva Povolný, 2001 with S. (H.) haemorrhoa Meigen, 1826, syn. nov.; Heteronychia (Spatulapica) fraterna Lehrer, 1977 with S. (H.) helenae (Trofimov, 1948), syn. nov.; Spatulapica delicata Lehrer, 2000 with S. (H.) helenae (Trofimov, 1948), syn. nov.; Heteronychia dayani Lehrer, 1996 with S. (H.) kerteszi Villeneuve, 1912, syn. nov.; Salemea sororia Povolný, 2004 with S. (H.) kerteszi Villeneuve, 1912, syn. nov.; Heteronychia (Eupierretia) helanshanensis Han, Chao & Ye, 1985 with S. (H.) kozlovi (Rohdendorf, 1937), syn. nov.; Sarcophaga thalhammeri Böttcher, 1913 with S. (H.) lacrymans Villeneuve, 1912, syn. nov.; Sarcophaga zhelochovtzevi Rohdendorf, 1925 with S. (H.) lacrymans Villeneuve, 1912, syn. nov.; Heteronychia (Heter- onychia) cepelaki Povolný & Slamečková, 1970 with S. (H.) lacrymans Villeneuve, 1912, syn. nov.; Heteronychia histriops Lehrer, 2008 with S. (H.) lacrymans Villeneuve, 1912, syn. nov.; Heteronychia (Eupierretia) brachystylata Chao & Zhang, 1988 with S. (H.) plotnikovi Rohdendorf, 1925, syn. nov.; Heteronychia lednicensis Povolný in Povolný & Verves, 1986 with S. (H.) proxima Rondani, 1860, syn. nov.; Heteronychia (Heteronychia) drenskiana Lehrer, 1977 with S. (H.) pseudobenaci (Baranov, 1942), syn. nov.; Heteronychia (Eupierretia) peckae Verves, 1977 with S. (H.) shnitnikovi (Roh-dendorf, 1937), syn. nov.; Heteronychia (Eupierretia) tenupenialis Chao & Zhang, 1988 with S. (H.) shnitnikovi (Rohdendorf, 1937), syn. nov.; Heteronychia (Pandelleola) volcanoaetnica Povolný, 2002 with S. (H.) sicilia Pape, 1996, syn. nov.; Hartigia anastrenua Baranov, 1942 with S. (H.) vagans Meigen, 1826, syn. nov. Lectotypes are designated for the following nominal taxa: Mehria pseudobenaci Baranov, 1942, Pierretia (Pierretia) boettcheriana Rohdendorf, 1937, Pierretia (Pierretia) obscurata Rohdendorf, 1937, Sarcophaga benaci Böttcher, 1913, Sarcophaga benaci var. tenuiforceps Böttcher, 1913, Sarcophaga boettcheri Villeneuve, 1912, Sarcophaga ferox Villeneuve, 1908, Sarcophaga fertoni Villeneuve, 1911, Sarcophaga kerteszi Villeneuve, 1912, Sarcophaga lacrymans Villeneuve, 1912, Sarcophaga metopina Villeneuve, 1908, Sarcophaga monspellensia Böttcher, 1913, Sarcophaga porrecta Böttcher, 1913, Sarcophaga setinervis var. mutila Villeneuve, 1912, Sarcophaga thalhammeri Böttcher, 1913 and Sarcophaga tricolor Villeneuve, 1908. Sarcophaga smithiana Pape, 1996 is removed from subgenus Heteronychia and considered as incertae sedis within Sarcophaga. New country or regional records are provided for Sarcophaga (H.) benaci (Spain), S. (H.) boettcheri (Serbia), S. (H.) croca (Croatia), S. (H.) depressifrons (Greece, Spain), S. (H.) ferox (Algeria), S. (H.) filia (Crete, Macedonia, Morocco, Tunisia), S. (H.) kataphygionis (Poland), S. (H.) kerteszi (Crete), S. (H.) minima (Crete), S. (H.) monspellensia (Sicily, Tunisia), S. (H.) mutila (Italy), S. (H.) nanula (France, Macedonia) and S. (H.) proxima (Sicily).